Vitamin D status during pregnancy and risk of multiple sclerosis in offspring of women in the Finnish Maternity Cohort - Munger, Kassandra L. (JAMA Neurol, 2016)
IMPORTANCE: Vitamin D has been associated with a decreased risk of multiple sclerosis (MS) in adulthood; however, some, but not all, previous studies have suggested that in utero vitamin D exposure may be a risk factor for MS later in life. OBJECTIVE: To examine whether serum 25-hydroxyvitamin D (25(OH)D) levels in early pregnancy are associated with risk of MS in offspring. DESIGN: Prospective, nested case-control study SETTING: Finnish Maternity Cohort (FMC) PARTICIPANTS: We identified 193 individuals with a diagnosis of MS before December 31, 2009 whose mothers are in the FMC and had an available serum sample from the pregnancy with the affected child. We matched 176 cases with 326 controls on region of birth in Finland, date of maternal serum sample collection, date of mother's birth, and date of child's birth. EXPOSURES: Serum 25(OH)D levels were measured in the maternal samples using a chemiluminescence assay. MAIN OUTCOMES AND MEASURES: Main outcome was the risk of MS associated with 25(OH)D levels. Conditional logistic regression was used, further adjusted for sex of the child, and gestational age and season of sample collection to estimate the relative risks and 95% confidence intervals. RESULTS: Over 70% of serum samples were collected during the first trimester of pregnancy and average maternal vitamin D levels were in the insufficient vitamin D range, but higher in maternal control than case samples (37.5 vs. 34.6 nmol/L). Maternal vitamin D deficiency (25(OH)D levels <30 nmol/L) during early pregnancy was associated with a nearly 2-fold increased risk of MS in the offspring (relative risk=1.90, 95% confidence interval: 1.20-3.01, p=0.006) as compared to women who were not deficient. Overall, risk of MS tended to decrease with increasing serum 25(OH)D levels, but the linear trend was not statistically significant (p=0.12). CONCLUSIONS AND RELEVANCE: Insufficient maternal 25(OH)D during pregnancy may increase the risk of MS in offspring.